Attitudes towards indirect translation in Finland and translators’ strategies: Compilative and collaborative translation - Ivaska Laura; Paloposki Outi (Taylor & Francis, 2022)
In Finland, indirect translation (ITr) played an important role as early as the sixteenth century in the formation of literary language. In the late nineteenth century, the first signs of critics condemning ITr began to appear. The stigma of ITr and the focus on the original have cast into obscurity the agency of translators and publishers, but archival material since the nineteenth century shows that publishers gave a free hand to translators doing ITr, who resorted to compilative translation. Kyllikki Villa, an important mediating agent and a translator of Modern Greek literature into Finnish during the second half of the twentieth century, discussed ITr as both translator and critic. Her archival material offers a rich insight into how her attitude towards ITr changed with her role: as a critic, she was wary of ITr; as a translator, she used and advocated compilative and collaborative translation as strategies for dealing with ITr.